(untitled) (Forum for Linguistic Studies, 2024)
Abstract. In This article explores enhancing responsibility in nature conservation amidst worsening ecological conditions. It emphasizes the complex nature of developing eco-ethical competence, encompassing ecological knowledge, skills, and responsibility formation. The integration of social interactions into educational methods to recognize ecological aspects across societal development stages is highlighted. The article underscores the need for cohesive approaches in educational systems to meet ecological demands effectively, utilizing integrative methods that enhance learning efficiency and foster positive changes. It concludes by stressing the importance of integrating ecological ethics seamlessly into educational frameworks to cultivate responsible ecological behavior among students.